Recent Advances in Design of Gold-Based Catalysts for H2 Clean-Up Reactions - Tabakova, Tatyana (Frontiers in Chemistry, 2019)
Over the past three decades, supported gold nanoparticles have demonstrated outstanding properties and continue to attract the interest of the scientific community. Several books and comprehensive reviews as well as numerous papers cover a variety of fundamental and applied aspects specific to gold-based catalyst synthesis, characterization by different techniques, relationship among catalyst support features, electronic and structural properties of gold particles, and catalytic activity, reaction mechanism, and theoretical modelling. Among the Au-catalysed reactions targeting environmental protection and sustainable energy applications, particular attention is paid to pure hydrogen production. The increasing demands for high-purity hydrogen for fuel-cell systems caused a renewed interest in the water-gas shift reaction. This well-known industrial process provides an attractive way for hydrogen generation and additional increase of its concentration in the gas mixtures obtained by processes utilizing coal, petroleum, or biomass resources. An effective step for further elimination of CO traces from the reformate stream after water-gas shift unit is the preferential CO oxidation. Developing highly active, stable, and selective catalysts for these two reactions is of primary importance for efficient upgrading of hydrogen purity in fuel cell applications. This review aims to extend the existing knowledge and understanding of the properties of gold-based catalysts for H2 clean-up reactions. In particular, new approaches and strategies for design of high performing and cost-effective formulations are addressed. Emphasis is placed on efforts to explore appropriate and economically viable supports with complex composition prepared by various synthesis procedures. Relevance of ceria application as a support for a new generation WGS catalysts is pointed out. The role of the nature of support in catalyst behavior, and specifically the existence of an active gold–support interface is highlighted. Long-term stability and tolerance toward start-up/shut down cycling is discussed. Very recent advances in catalyst design are described focusing on structured catalysts and microchannel reactors. Latest mechanistic aspects of the water-gas shift reaction and preferential CO oxidation over gold-based catalysts from density functional theory calculations are noted because of their essential role in discovering novel highly efficient catalysts.